Kuwait’s on-going debate on gender-segregation in schools - Nature Research (16552612) (2016)
People who attended gender-segregated and mixed-gender schools in Kuwait perceive their relationships with peers of the opposite sex differently, according to a study by Lujain AlMatrouk, an educational diagnostician with the Center for Child Evaluation and Teaching in Kuwait. Seventy-six people who lived and went to school in Kuwait responded to an online questionnaire that aimed to assess whether gender segregation in schools affected peer relations with the opposite sex and to explore what factors might influence this effect. Gender segregation is imposed in Kuwaiti public schools, and public and private universities. Currently, only private schools are exempted. There’s an ongoing debate in the country about the pros and cons of gender segregation. The topic has been an area of study for many researchers around the world. One researcher showed that gender segregation produces higher grades. Others, however, showed mixed-gender schools in Belgium, where the majority of schools are segregated, produced the best academic results. Also, some researchers argue that gender segregation allows children to focus on learning without worrying about bullying from the opposite sex while another found a high level of bullying among girls3. “Studies on the effects of gender segregation in the Arab world are limited, yet very important, as a majority of the schools in the Arab region are gender-segregated owing to conservative beliefs,” writes AlMatrouk in her study published in the Near and Middle Eastern Journal of Research in Education. AlMatrouk found that perceptions varied between people who attended gender-segregated and mixed-gender schools in Kuwait about their relationships with peers of the opposite sex “should be taken into consideration when creating educational policies for schools in Kuwait and debating issues related to gender segregation,” she writes. She also found that the stronger one’s self-esteem, the better respondents perceived their relationships with peers of the opposite sex. Also, the stronger respondents perceived their relationship with their parents, the more self-esteem they had. “Therefore, parental interventions should be designed for Arab parents at schools in Kuwait in order to raise awareness about the importance of parental relations on self-esteem,” she writes. AlMatrouk acknowledges the limitations of her study, including the small sample size, the fact that the questionnaire was in English and not in Arabic, and the fact that the sample was not representative of the society-at-large (in terms of male/female ratio of respondents, the high number of single respondents, and the comparatively small number of respondents who went to gender-segregated schools [16/76]). Other Information Published in: QScience.com Highlights, Published by Nature Research for Hamad bin Khalifa University Press (HBKU Press) License: http://creativecommons.org/licenses/by/4.0